(untitled) (Journal of Medical & Health Sciences Review, 2025)
Depression is a highly prevalent mental health condition affecting millions worldwide, including medical students who face unique stressors. This study aimed to assess the relationship between excessive daytime sleepiness and depression among medical students in various institutions across Pakistan. A semi-structured questionnaire was administered to 151 medical students. Responses were evaluated using validated scales including the Pittsburgh Sleep Quality Index (PSQI), Patient Health Questionnaire-9 (PHQ-9), Epworth Sleepiness Scale (ESS), and Suicidal Ideation Attributes Scale (SIDAS). Each scale assessed specific parameters such as depression severity, sleep quality, and suicidal ideation. While no statistically significant direct association was found between excessive daytime sleepiness and either depression or suicidal ideation, an indirect relationship was observed. Notably, poor sleep quality and reduced sleep duration were significantly associated with higher scores on depression and suicidality scales. In conclusion, although a direct link between daytime sleepiness and depression was not established, sleep quality and duration appear to indirectly influence depressive symptoms and suicidal thoughts among medical students.